Escepticismo y mundo de la vida. El problema de la obligatoriedad de las reglas del discurso en la pragmática trascendental - Leandro Paolicchi (Ideas y Valores)
The article addresses the fundamental problem of the transcendental pragmatics of language, as well as the issue of the ethics of discourse developed by K.-O. Apel and J. Habermas, a matter referred to the obligatoriness of the rules of discourse. Attention is focused on the objection posed by Habermas, which restricts the scope of the obligatory nature of those rules. After analyzing the objection and the solution proposed by Habermas, we offer an interpretation of his response.